Unlock the thermogenic potential of adipose tissue: pharmacological modulation and implications for treatment of diabetes and obesity - Peng, Xiao-Rong; Gennemark, Peter; O'Mahony, Gavin; Bartesaghi, Stefano (Frontiers in Endocrinology, 2015)
Brown adipose tissue (BAT) is considered an interesting target organ for the treatment of metabolic disease due to its high metabolic capacity. Non-shivering thermogenesis, once activated, can lead to enhanced partitioning and oxidation of fuels in adipose tissues, and reduce the burden of glucose and lipids on other metabolic organs such as liver, pancreas and skeletal muscle. Sustained long-term activation of BAT may also lead to meaningful bodyweight loss. In this review, we discuss three different drug classes (the thiazolidinedione (TZD) class of PPAR agonists, 3 adrenergic receptor agonists and fibroblast growth factor 21 (FGF21) analogues) that have been proposed to regulate BAT and beige recruitment or activation, or both, and which have been tested in both rodent and human. The learnings from these classes suggest that restoration of functional BAT and beige mass as well as improved activation might be required to fully realize the metabolic potential of these tissues. Whether this can be achieved without the undesired cardiovascular side-effects exhibited by the TZD PPAR agonists and 3 adrenergic receptor agonists remains to be resolved.